(untitled) (International Journal of Gender, Science and Technology, 2015)
The number of international students in graduate school within STEM fields at US institutions has risen dramatically over the last few decades, whereas the numbers of US women attending graduate school in STEM fields has largely stagnated. These trends suggest the importance of intersectionality to understanding individuals’ pursuit of STEM careers. Here we examined doctoral (N = 270) and postdoctoral (N = 27) students' satisfaction with their graduate training at a large, research-focused institution in the US as a function of the intersection of participants’ gender and nativity. Participants completed measures of occupational values, perceived fit of their values with STEM research careers, perceptions of discrimination, mentor support, and satisfaction with their graduate training. Results indicated that international and US-born women both valued family flexibility more than did international and US-born men. Importantly, international, but not US-born, women viewed careers in STEM research as affording, or providing a means of fulfilling, their values. Furthermore, US women were more likely than international women to perceive their gender as the target of discrimination. Stronger belief that research careers do not&provide a means of fulfilling&one’s values and greater perceptions of gender discrimination were associated with lower ratings of satisfaction with graduate training among women but not men.